Sustainable Valorisation and Efficient Downstream Processing of Giant Reed by High‐Pressure Carbon Dioxide Pretreatment. Issue 10 (23rd August 2022) - Di Fidio, Nicola; Tozzi, Federico; Martinelli, Marco; Licursi, Domenico; Fulignati, Sara; Antonetti, Claudia; Raspolli Galletti, Anna Maria
Abstract: This work investigated the catalytic high‐pressure CO2 pretreatment of giant reed. CO2 is a renewable resource; its use does not generate chemical wastes and it can be easily removed and recycled. The effect of the addition of low concentrations of FeCl3 (0.16 wt %) and PEG 400 (1.0 wt %) on the hemicellulose hydrolysis to xylose and xylo‐oligosaccharides (XOS) is reported for the first time. Under the optimised pretreatment conditions, the xylan conversion of 82 mol % and xylose and XOS yields of 43 and 20 mol % were achieved, respectively. The solid residues obtained from different pretreatments were used as the substrate for the enzymatic hydrolysis to give glucose. The total glucose yield achieved under the optimised two‐step process was 67.8 mol % with respect to the glucan units in the biomass. The results demonstrated that PEG‐assisted FeCl3 ‐catalysed scCO2 pretreatment can produce xylose‐ or XOS‐rich hydrolysates and improve the enzymatic hydrolysis of biomass. Abstract : An innovative optimised catalytic high‐pressure carbon‐dioxide pretreatment of giant reed is reported in this work, involving the synergistic addition of very low amounts of catalyst (FeCl3 ) and surfactant (polyethylene glycol 400), followed by enzymatic hydrolysis employing the commercial enzymatic mixture Cellic ® CTec3 HS, in order to produce valuable and concentrated sugar‐rich hydrolysates.